Analysis of Curcuma Tablet Use in TB Patients with Liver Dysfunction and Factors Influencing Treatment Success: Analysis of Curcuma Tablet Use in TB Patients with Liver Dysfunction and Factors Influencing Treatment Success - umi fatma wati; Fahmi Dimas Abdul Aziz; Rasyidin Rumulus (JURNAL FARMASI DAN MAKANAN, 2025)
Background: Tuberculosis (TB) is a global health problem, and anti-tuberculosis drugs (ATD) often cause hepatotoxic side effects (Drug-Induced Liver Injury/DILI). Turmeric (temulawak) with its curcumin content has the potential to be a hepatoprotector. This study aims to analyze the use of Curcuma tablets and the factors influencing the success of therapy in TB patients with impaired liver function. Methods: This study uses a retrospective cohort design with a Cost-Effectiveness Analysis (CEA) approach. A sample of 70 TB patients with DILI at Dr. Soetomo General Hospital Surabaya from January to December 2024 was taken using consecutive sampling. Demographic, clinical, laboratory (SGOT, SGPT), and data were extracted from electronic medical records. Data analysis was performed using univariate, bivariate (Chi-Square), and multivariate (logistic regression) tests. Results: The research results showed that the majority of participants were male (75.7%), with the largest age groups being between 51-60 years and >60 years (32.9% each). Residing in Surabaya (52.9%). The majority of patients were normal weight (55.7%), had a history of smoking (52.9%), did not have a history of diabetes mellitus (67.1%), and had a history of hypertension (82.9%). The BTA examination result was positive (55.7%) and the TCM result was "MTB Detected Rifampicin Sensitive" (61.4%). Undergoing therapy with the OAT 4 FDC regimen or intensive phase (65.7%) in the intensive phase (90%). The most common length of stay was between 6-10 days (34.3%), and the most frequent therapeutic outcome was improvement (78.6%). Based on the bivariate data analysis, only one variable had a p-value < 0.05, which was age, indicating a significant relationship with the treatment outcome. Patients aged 51-60 and > 60 years old influenced the treatment outcome with a p-value of 0.016, which is less than α (p < 0.05). Conclusion: The research findings indicate that gender, smoking history, diabetes mellitus history, hypertension history, BTA test results, TCM (Molecular Rapid Test) results, length of hospital stay, and duration of curcuma tablet administration did not show a significant relationship with treatment outcome. Age, domicile, BMI (Body Mass Index), treatment phase, and OAT (Anti-TB Drug) therapy regimen showed a significant relationship with treatment outcome. Age is the most influential risk factor for treatment outcome. Further research with a larger and multi-center sample is recommended to strengthen the findings.Keywords: Curcuma, DILI, Pulmonary TB, Hepatoprotector.